General Practitioner who Provides Aesthetic Services from an Indonesian Law Perspective - Yeo, Susilo Kurniawan (SASI, 2023)
Introduction: While there is a high demand for aesthetic services in Indonesia, the regulations governing them have yet to be fully established. As a result, general practitioners who wish to offer these services must navigate a complex legal landscape. This article explores the legal aspects for general practitioners looking to provide aesthetic services in Indonesia, offering valuable insights for those seeking to enter this growing field.Purposes of the Research: This study aims to analyze the position and status of general practitioners who provide aesthetic services in Indonesia.Methods of the Research: To achieve these objectives, the author uses normative legal research methods with analytical approach. This study uses secondary data consisting of primary legal materials and secondary legal materials obtained through literature study.Results of the Research: The results of the study indicate that general practitioners are allowed to provide aesthetic services in accordance with defined and undefined competencies if they have attended education and training for these competencies which is organized by professional association and other institutions accredited by professional association.